EFAS Score - validation of Finnish and Turkish versions by the Score Committee of the European Foot and Ankle Society (EFAS) - IRGIT, KAAN SÜLEYMAN (ELSEVIER, 2020)
Background: The Score Committee of the European Foot and Ankle Society (EFAS) developed, validated, and published the EFAS Score in seven European languages (English, German, French, Italian, Polish, Dutch, Swedish). From other languages under validation, the Finnish and Turkish versions finished data acquisition and underwent further validation. Methods: The EFAS Score was developed and validated in three stages: 1) item (question) identi fication (completed during initial validation study), 2) item reduction and scale exploration (completed during initial validation study), 3) con firmatory analyses and responsiveness of Finnish and Turkish version (completed during initial validation study in seven other languages). The data were collected pre- operatively and post -operatively at a minimum follow-up of 3 months and mean follow-up of 6 months. Item reduction, scale exploration, con firmatory analyses and responsiveness were executed using classical test theory and item response theory. Results: The internal consistency of the scale was con firmed in the Finnish and Turkish versions (Cronbach's Alpha 0.8). Responsiveness was good, with moderate to large effect sizes in both languages, and evidence of a statistically signi ficant positive association between the EFAS Score and patient - reported improvement. Conclusions: The Finnish and Turkish EFAS Score versions were successfully validated in the orthopaedic ankle and foot surgery patients, including a wide variety of foot and ankle pathologies. All score versions are freely available at www.efas.co. (C) 2020 European Foot and Ankle Society. Published by Elsevier Ltd. All rights reserved.
Keywords: Score; Foot; Ankle; Validation; PROM